The Effect Of External Audit Quality On Profit Management - Tawfiq Shibli, Abdul Hussein; Ibrahim Saleh, Jalil; Abdul Rahman, Nahla Ghaleb (Opción, 2019)
This study aims to identify the extent of the practice of Iraqi industrial compa- nies listed in the Iraq Stock Exchange for profit management on the one hand, and on the other hand to identify the most important factors that affect the practice of profit management and the characteristics of audit quality (the size of the audit office, the period of customer retention, the audit office link With global auditing offices, specializing in the customer’s industry, audit fees), and showing the type of relationship between each of the characteristics of audit quality and profit management, and to achieve the goals of the study a model was built to measure the relationship between the quality of the audit quality and the profit tool, and many methods were used Statistics such as Binomial Test for the first major silver test, and Binary Logit to test the other five hy- potheses. One of the findings of the study is that the Iraqi industrial companies listed on the Iraq Stock Exchange exercise profit management during the var- ious study years for the period of (2012-2017), despite the presence of variance during those years, and this is clearly shown in my two years (2016-2017) As the year 2016 was the lowest year in the practice of profit management, as the practice rate reached 16% of the sample companies, and in contrast, the year 2017 was one of the sharpest years in the practice of profit management, as the practice rate reached 64% of the sample companies, as well as “ There is a statistically significant effect for each property (independent variable) of the quality of the audit On the practice of profit management, while there is no statistically significant effect of the association of the audit office with global auditing offices on the practice of profit manage- ment, and in light of the results of the study, the researchers recommend- ed a number of recommendations, the most important of which is the es- tablishment of a control committee that works to provide a high-quality audit environment that works to limit practices Unwanted practices such as profit management practice, as well as making investors and corporate departments aware of the negative effects of profit management practices on their investment decisions.